(untitled) (World Bulletin of Social Sciences, 2024)
The article examines the problems of interpersonal conflicts among teachers in educational institutions, the main causes of conflict situations, as well as examples of the most common interpersonal conflicts in the teaching staff. Unfortunately, interpersonal conflicts in relationships among teachers have been studied to a lesser extent compared to other types of conflicts in school collectives. This is due to the fact that conflicts between teachers are much more complex and diverse than conflicts involving schoolchildren